The Correlation of Students’ Personality, Learning Style and Achievement in English - Mustari, Ichwan; Nur, Sahril; Amin, Fatimah Hidayahni; Mansur, Musdalifah; Safaitri, Citra Dwi (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This research aims to determine the relationship between students' personalities, learning styles, and achievements in learning English among XI.7 grade students at SMAN 1 Bantaeng. This research uses a correlational research design. The study used a personality questionnaire from Airasian and Gay to investigate students' personalities. It also employed a learning style questionnaire by Joy M Reid to investigate students' learning styles. It then confirmed the student achievement scores from English teachers. The population of this research was all students at level XI.7 of SMAN 1 Bantaeng and they were selected randomly with 25 students from one class. After analyzing the student personality using SPSS, it was found that introvert personalities with a visual learning style scored 0.786, introvert personalities with an audio learning style scored 0.914, introvert personalities with a kinesthetic learning style scored 0.874 as well as extrovert personalities with a visual learning style scored 0.944, extrovert personalities with an audio learning score 0.926, extrovert personality with a kinesthetic learning style score of 0.927. Thus, academic success in English is significantly correlated with introverted students with a Visual Auditory Kinesthetic learning style and is significantly correlated with extroverted students whose learning style shows a good correlation.